The Implementation of Numbered Head Together (NHT) in Improving Reading Comprehension Skill of The Eight Grade Students of SMP Negeri 16 Banda Aceh - Venti Rifka Oulia (Universitas Serambi Mekkah, 2021)
Students’ reading comprehension skill in English is influenced by the methods used by the English teacher in class. The aims of the study are: 1) to find out improvement of students at SMP Negeri 16 Banda Aceh in reading comprehension after they were taught by using NHT, and 2) to find out if there is a significant difference between the students’ taught by using NHT and those taught without using it. The result of this study showed that the t-score of two means between post-test of experimental and control group was 2.15; thus, the t -test is higher than critical value of t-test for the degree freedom of 58 (2.00) at the level of significance 0.05. Based on the result of the study, the English teachers of SMP Negeri 16 Banda Aceh were encouraged to use NHT (Numbered Heads Together) in teaching reading comprehension because it can increase the students' ability in mastering the subject. It means that there is a significant difference between the students’ ability of SMP Negeri 16 Banda Aceh taught by using NHT and those taught without it in mastering reading comprehension.